(3QSGdI aj CSdhH GdMcjes - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdYdje GdMcjeCeG HYO agPg QSGdI QJHfGgG aj HjGf CSdhH GdMcje hJejjRg Yf SGFQ GdCSGdjH GdeYJHQIs
(3BNQgG (B:s
(3eKd Pdc GdMed ef dWGFa GdeYGfj ceG aj GdCSdhH GdMcje efgG Hd YO ef GdeMSfGJ GdHOjYjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 133s
(3eYLe GdeDdajf(B: 1 / 148s
(3cTa GdXfhf(B: 1 / 846s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdHdGZIs